2020
DOI: 10.1177/2324709620912122
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Fungal Burn Wound Infection Caused by Fusarium solani in Vietnam

Abstract: A patient with extensive burn injuries was admitted to the National Hospital of Burns in Hanoi, Vietnam, and diagnosed with fungal wound infection by histological examination of skin biopsy samples. Fusarium solani was isolated and identified by analysis of its morphological features and the sequence of the internal transcribed spacer region. The isolation showed in vitro resistant to fluconazole, voriconazole, itraconazole, amphotericin B, and caspofungin. Invasive fusariosis is difficult to treat due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Among them, 28 case series and 15 irrelevant studies were excluded. Finally, 36 case reports encompassing 44 burn patients were included for the final analysis 10–45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 28 case series and 15 irrelevant studies were excluded. Finally, 36 case reports encompassing 44 burn patients were included for the final analysis 10–45 …”
Section: Resultsmentioning
confidence: 99%
“…In 36 of the 44 cases, fungal infections were initially suspected and identified from the burn wound samples 10–27,31–33,35–37,39–45 . In the remaining 8 cases, presentations of fungal wound infection were not observed, whereas invasive fungal infections were found in other sites such as blood, arterial thrombosis, teeth, feces, urine, sputum, and tracheal fluid 28–30,34,38 …”
Section: Resultsmentioning
confidence: 99%
“…In this study, the most common fungus isolated from wounds was Fusarium . As a plant pathogen, Fusarium widely exists in natural environments, particularly in soil [ 25 ]. However, a study in Vietnam reported that humans could also be infected by the fungus through burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…FSSC, F. solani species complex (SC); FFSC, F. fujikuroi SC; FOSC, F. oxysporum SC; FNSC, F. nisikadoi SC; FIESC, F. incarnatum-equiseti SC; FDSC, F. dimerum SC; FCSC, F. chlamydosporum SC. 10.3389/fmicb.2022.992582 Frontiers in Microbiology 08 frontiersin.org 2006; Pai et al, 2010;Atty et al, 2014;Rosanova et al, 2016;Karadag et al, 2020;Tram et al, 2020;Liza et al, 2021). We observed 63.2% (24/38) of isolates from skin secretions belonged to FSSC.…”
Section: Discussionmentioning
confidence: 99%
“…Severe burns and poorly controlled diabetes are thought to be high risk factors for invasive mold infections ( Nucci and Anaissie, 2007 ; Enoch et al, 2017 ). However, little is known about the epidemiology of Fusarium strains causing locally invasive skin infection in patients with burns or diabetes mellitus, limited by sporadic case reports ( Nucci and Anaissie, 2002 ; Taj-Aldeen et al, 2006 ; Pai et al, 2010 ; Atty et al, 2014 ; Rosanova et al, 2016 ; Karadag et al, 2020 ; Tram et al, 2020 ; Liza et al, 2021 ). We observed 63.2% (24/38) of isolates from skin secretions belonged to FSSC.…”
Section: Discussionmentioning
confidence: 99%